Europäisches Strafrecht post-Lissabon - Ambos, Kai (Universitätsverlag Göttingen, 2011)
This volume deals with the future of European criminal law under the Lisbon Treaty. The contributions assess the risks and prospects of the progressing European integration with a special focus on the enlarged competences of the EU in the field of criminal law.